The Influence of Transformational Leadership, Organizational Culture, and Work Motivation on Employee Performance in a West Java Manufacturing Company - Abdullah Faqih; Hartono, Edy (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This research investigates the extent to which transformational leadership, organizational culture, and work motivation contribute to employee performance within the production division of a manufacturing firm located in West Java. A quantitative associative research design was adopted for this study. The entire population of 127 production employees was included as study participants through a census approach. Primary data were gathered using a structured questionnaire instrument, while hypothesis testing was conducted through multiple linear regression analysis with the aid of SPSS version 22.0. The results indicate that organizational culture (β = 0.208; p = 0.001) and work motivation (β = 0.151; p = 0.036) have a positive and significant effect on employee performance. In contrast, transformational leadership (β = 0.014; p = 0.896) shows a positive but insignificant effect. Simultaneously, all variables significantly influence performance (F = 19.756; p = 0.000), with an R² value of 0.325. These findings highlight that organizational culture and motivation are key drivers of employee performance, while the role of transformational leadership may depend on the structural characteristics of the organization.